Electrode assembly, battery cell, battery and electric device

By providing a high content of a polar functional group-containing adhesive coating on the negative electrode side of the porous substrate, the battery reliability and life problems caused by dendrites are solved, and a battery design with high Coulomb efficiency and good circulation performance is achieved.

CN120261913APending Publication Date: 2025-07-04CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410002271.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-01-02
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

Battery reliability and service life problems caused by dendrite growth during battery charging and discharging include electrolyte consumption, reduced Coulomb efficiency, diaphragm puncture and internal short circuit risk.

Method used

A coating containing a first binder is provided on the negative electrode side of the porous substrate. The first binder contains poly(meth)acrylic acid, lithiated salt, sodium salt and modified polymer, with a weight percentage content greater than 40 wt%. By reacting polar functional groups with dendrites, the probability of dendrites formation is reduced and the ion conduction ability is improved.

Benefits of technology

Slows down dendrites, reduces the risk of internal short circuits of batteries, improves battery reliability, Coulomb efficiency and cycling performance, and is suitable for lithium and sodium metal batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120261913A_ABST
    Figure CN120261913A_ABST
Patent Text Reader

Abstract

The invention discloses an electrode assembly, a battery monomer, a battery and a power utilization device, the electrode assembly comprises a positive pole piece, a negative pole piece and an isolating membrane, the isolating membrane comprises a porous base material and a first coating at least located on one side, close to the negative pole piece, of the porous base material; the first coating comprises a first binder, and the first binder comprises one or more of poly (methyl) acrylic acid, lithiated salt of the poly (methyl) acrylic acid, sodium salt of the poly (methyl) acrylic acid and modified polymer obtained by carrying out a modification process on the polymer; and the weight percentage of the first binder in the first coating is greater than or equal to 40wt%. According to the invention, dendritic crystal growth can be slowed down, the dendritic crystal formation probability is reduced, and the battery has high coulombic efficiency, good cycle performance and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to an electrode assembly, a battery cell, a battery, and an electrical device. Background Art

[0002] With the application and popularization of batteries, their reliability and service life have received increasing attention. During the charge and discharge process of the battery, the dendrite problem on the negative electrode is one of the important reasons affecting the reliability and service life of the battery. During the charge and discharge process of the battery, dendrite growth will continuously consume the electrolyte and active ions, thereby reducing the capacity and Coulomb efficiency of the battery; during the dendrite growth process, fracture problems may also occur. The fractured dendrites lose electron contact with the negative electrode current collector, and thus will no longer contribute to the capacity, further reducing the capacity and Coulomb efficiency of the battery; continuous dendrite growth may also pierce the separator, resulting in internal short circuit of the battery, and even causing the battery to catch fire and explode. How to slow down dendrite growth without affecting the electrochemical performance and / or kinetic performance of the battery is a technical problem that needs to be solved urgently at present. Summary of the Invention

[0003] The present application provides an electrode assembly, a battery cell, a battery, and an electrical device, which can slow down dendrite growth, reduce the probability of dendrite formation, and enable the battery to have high reliability, high Coulomb efficiency, good cycle performance, and rate performance.

[0004] In a first aspect, the present application provides an electrode assembly, including a positive electrode sheet, a negative electrode sheet, and a separator. The separator includes a porous substrate and at least a first coating located on one side of the porous substrate close to the negative electrode sheet. The first coating includes a first binder, and the first binder includes one or more of poly(meth)acrylic acid, a lithiated salt of poly(meth)acrylic acid, a sodium salt of poly(meth)acrylic acid, and a modified polymer obtained by modifying the foregoing polymer. The weight percentage content of the first binder in the first coating is greater than or equal to 40 wt%.

[0005] The first coating includes a first binder, and the first binder includes one or more of poly(meth)acrylic acid, a lithiated salt of poly(meth)acrylic acid, a sodium salt of poly(meth)acrylic acid, and a modified polymer obtained by modifying the foregoing polymer. The first binder contains polar functional groups, such as -COOH, etc. Therefore, the first binder can better bond the electrode sheet and the separator, and bond the porous substrate and the first coating, thereby ensuring the tightness of the electrode assembly.

[0006] By providing at least a first coating containing a first binder on the negative electrode side of the porous substrate, since the first binder contains polar functional groups such as -COOH, etc., the compatibility between the separator and the electrolyte can be improved, the wettability of the separator to the electrolyte can be enhanced, and the ion transport impedance of the separator can be reduced.

[0007] The weight percentage of the first binder in the first coating of the separator membrane is greater than or equal to 40 wt%. Due to the high content of the first binder, at this time, in addition to playing a binding role, the first binder can also react with lithium dendrites, sodium dendrites, etc. generated on the surface of the negative electrode through polar functional groups such as -COOH to eliminate dendrites; and the products after the reaction of the first binder with lithium dendrites, sodium dendrites, etc. also have good ion conduction ability, so that the ion flow on the surface of the negative electrode can be made uniform, the ion concentration difference on the surface of the negative electrode can be alleviated, and thus the probability of dendrite formation can be reduced.

[0008] The separator membrane provided by the embodiment of the present application can achieve the effects of slowing down dendrite growth and reducing the probability of dendrite formation. Therefore, the risk of internal short circuit of the battery can be reduced, the reliability of the battery can be improved, the Coulomb efficiency and the cycle capacity retention rate of the battery can be improved, and the battery can be charged at a high rate. Therefore, the separator membrane provided by the embodiment of the present application can endow the metal battery with high reliability, high Coulomb efficiency, good cycle performance and rate performance.

[0009] In some embodiments, the weight percentage of the first binder in the first coating is 40 wt% - 60 wt%.

[0010] By adjusting the weight percentage of the first binder in the first coating within the above range, the battery can have high Coulomb efficiency and cycle capacity retention rate while having good rate performance.

[0011] In some embodiments, the modification methods include one or more of block copolymerization modification, graft copolymerization modification, filling modification, and polymer melt blending modification.

[0012] In some embodiments, the first binder includes one or more of polyacrylic acid, polymethacrylic acid, partial lithium salts of polyacrylic acid, partial lithium salts of polymethacrylic acid, partial sodium salts of polyacrylic acid, partial sodium salts of polymethacrylic acid, polyacrylic acid-g-sodium carboxymethyl cellulose, partial lithium salts of polyacrylic acid-g-sodium carboxymethyl cellulose, partial sodium salts of polyacrylic acid-g-sodium carboxymethyl cellulose, poly(acrylic acid-g-vinylidene fluoride), poly(acrylic acid-g-vinyl alcohol), partial lithium salts of polyacrylic acid-g-vinylidene fluoride, partial lithium salts of polyacrylic acid-g-vinyl alcohol, partial sodium salts of polyacrylic acid-g-vinylidene fluoride, partial sodium salts of polyacrylic acid-g-vinyl alcohol, polymethacrylic acid-g-sodium carboxymethyl cellulose, partial lithium salts of polymethacrylic acid-g-sodium carboxymethyl cellulose, partial sodium salts of polymethacrylic acid-g-sodium carboxymethyl cellulose, poly(methacrylic acid-g-vinylidene fluoride), poly(methacrylic acid-g-vinyl alcohol), partial lithium salts of polymethacrylic acid-g-vinylidene fluoride, partial lithium salts of polymethacrylic acid-g-vinyl alcohol, partial sodium salts of polymethacrylic acid-g-vinylidene fluoride, partial sodium salts of polymethacrylic acid-g-vinyl alcohol, amorphous calcium carbonate-polyacrylic acid hydrogel, polyacrylic acid-polyamideimide, ethylene-acrylic acid copolymer, butadiene-acrylic acid copolymer, styrene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, butadiene-methacrylic acid copolymer.

[0013] In some embodiments, the content of -COOH in the first binder is 0.005 mol / g - 0.012 mol / g.

[0014] By adjusting the content of -COOH in the first binder within the above range, the battery can have good rate performance while also having high Coulombic efficiency and cycle capacity retention rate.

[0015] In some embodiments, the total mass percentage content of -COOLi and -COONa in the first binder is 1% - 15%, based on the total mass of -COOH, -COOLi and -COONa being 100%.

[0016] By adjusting the total mass percentage content of -COOLi and -COONa in the first binder within the above range, the first binder can have good ion conduction ability, thereby better uniforming the ion flow on the negative electrode surface, alleviating the ion concentration difference on the negative electrode surface, further reducing the probability of dendrite formation, and further improving the cycle performance and rate performance of the battery.

[0017] In some embodiments, the weight-average molecular weight of the first binder is 50,000 - 800,000.

[0018] By adjusting the weight-average molecular weight of the first binder within the above range, the first binder can have good binding properties and good solubility, and is easily and uniformly dispersed in the slurry.

[0019] In some embodiments, the thickness of the first coating is 2 μm - 10 μm.

[0020] When the thickness of the first coating is within the above range, it can not only eliminate dendrites and slow down dendrite growth, but also reduce the irreversible consumption of active ions. As a result, the battery can have good rate performance, high Coulomb efficiency, and high cycle capacity retention rate.

[0021] In some embodiments, the first coating further includes first particulate inorganic fillers that can react with lithium metal and / or sodium metal.

[0022] By including first particulate inorganic fillers in the first coating, the separator can have high mechanical strength, good puncture resistance, and good heat resistance, thereby reducing the risk of internal short circuit in the battery and improving the reliability of the battery.

[0023] The first particulate inorganic fillers also have good electrolyte wettability. Therefore, when the first particulate inorganic fillers are used in the first coating, the compatibility between the separator and the electrolyte can be improved, the wettability of the separator to the electrolyte can be enhanced, and the ion transport impedance of the separator can be reduced, which is conducive to further improving the cycle performance and rate performance of the battery.

[0024] The first particulate inorganic fillers can react with lithium metal and / or sodium metal, and thus can also play a role in eliminating dendrites.

[0025] In some embodiments, the weight percentage content of the first particulate inorganic fillers in the first coating is 39 wt% - 59 wt%.

[0026] When the weight percentage content of the first particulate inorganic fillers in the first coating is within the above range, the first coating can have a good pore structure, improving the air permeability and electrolyte wettability of the separator, and the separator can also have high mechanical strength, good puncture resistance, and good heat resistance. As a result, the battery can have high reliability, high Coulomb efficiency, good cycle performance, and rate performance.

[0027] In some embodiments, the volume distribution particle size Dv50 of the first particulate inorganic fillers is 20 nm - 2000 nm.

[0028] When the volume distribution particle size Dv50 of the first particulate inorganic filler is within the above range, the first coating can have a good pore structure, improving the gas permeability and electrolyte wettability of the separator membrane. It can also make the first coating slurry have an appropriate viscosity, facilitating coating and enhancing the coating effect. Additionally, it can enable the first particulate inorganic filler to better adhere to the porous substrate, reducing powder shedding and pore plugging problems.

[0029] In some embodiments, the first particulate inorganic filler includes one or more of a solid electrolyte material, a metal oxide, a metal sulfide, a metal nitride, a non-metal oxide, a non-metal sulfide, a non-metal nitride, and a carbon-based material.

[0030] In some embodiments, the separator membrane includes a porous substrate, a first coating on one side of the porous substrate close to the negative electrode tab, and a second coating on one side of the porous substrate close to the positive electrode tab. The second coating includes a second binder and a second particulate inorganic filler.

[0031] This can better reduce the risk of internal short circuit of the battery caused by dendrite piercing through the separator membrane and contacting the positive electrode, and further improve the reliability of the battery.

[0032] In some embodiments, the weight percentage content of the second binder in the second coating is 0.1 wt% - 3 wt%, and the weight percentage content of the second particulate inorganic filler is 97 wt% - 99.9 wt%.

[0033] In some embodiments, the volume distribution particle size Dv50 of the second particulate inorganic filler is 20 nm - 2000 nm.

[0034] When the volume distribution particle size Dv50 of the second particulate inorganic filler is within the above range, the second coating can have a good pore structure, improving the gas permeability and electrolyte wettability of the separator membrane. It can also make the second coating slurry have an appropriate viscosity, facilitating coating and enhancing the coating effect. Additionally, it can enable the second particulate inorganic filler to better adhere to the porous substrate, reducing powder shedding and pore plugging problems.

[0035] In some embodiments, the thickness of the second coating is 0.5 μm - 5 μm.

[0036] When the thickness of the second coating is within the above range, it can better reduce the risk of internal short circuit of the battery caused by dendrite piercing through the separator membrane and contacting the positive electrode, and further improve the reliability of the battery. It can also make the separator membrane have good gas permeability, resulting in a smaller impedance of the battery, which is beneficial for the battery to have good cycling performance and rate performance.

[0037] In some embodiments, the second binder includes one or more of poly(meth)acrylic acid, vinylidene fluoride polymer, sodium carboxymethyl cellulose, styrene-butadiene rubber, and their respective derivatives.

[0038] In some embodiments, the second particulate inorganic filler includes ceramics. This can better reduce the risk of internal short circuit of the battery caused by dendrite piercing through the separator and contacting the positive electrode, and thus can further improve the reliability of the battery.

[0039] In some embodiments, the total thickness of the separator is 7 μm - 35 μm.

[0040] In some embodiments, the porosity of the separator is 25% - 50%.

[0041] When the total thickness and / or porosity of the separator are within the above ranges, the separator can have good ion conduction ability and low impedance.

[0042] In some embodiments, the thickness of the porous substrate is 5 μm - 25 μm.

[0043] In some embodiments, the porosity of the porous substrate is 25% - 60%.

[0044] When the thickness and / or porosity of the porous substrate are within the above ranges, the separator can have good ion conduction ability and low impedance.

[0045] In some embodiments, the porous substrate includes one or more of polyolefin, polyamide, polyester, cellulose, and their respective derivatives.

[0046] In a second aspect, the present application provides a battery cell, which includes the electrode assembly of the first aspect of the present application.

[0047] In some embodiments, the battery cell includes at least one of a lithium metal battery cell, a lithium metal battery cell without a negative electrode, a sodium metal battery cell, and a sodium metal battery cell without a negative electrode.

[0048] In a third aspect, the present application provides a battery, which includes the battery cell of the second aspect of the present application.

[0049] In a fourth aspect, the present application provides an electrical device, which includes the battery of the third aspect of the present application, and the battery is used to provide electrical energy.

[0050] The electrical device of the present application includes the battery provided by the present application, and thus has at least the same advantages as the battery. Description of the Drawings

[0051] To more clearly illustrate the technical solutions of the embodiments of the present application, the following will briefly introduce the drawings required for use in the embodiments of the present application. Obviously, the following described drawings are only some embodiments of the present application. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on the drawings.

[0052] Figure 1 The structural schematic diagram of a battery cell provided by some embodiments of the present application is shown.

[0053] Figure 2 The structural schematic diagram of a battery module provided by some embodiments of the present application is shown.

[0054] Figure 3 The structural schematic diagram of a battery pack provided by some embodiments of the present application is shown.

[0055] Figure 4 is Figure 3 The exploded schematic diagram of the battery pack shown.

[0056] Figure 5 The exploded schematic diagram of a battery cell provided by some embodiments of the present application is shown.

[0057] Figure 6 The structural schematic diagram of a separator provided by some embodiments of the present application is shown.

[0058] Figure 7 The structural schematic diagram of a separator provided by some other embodiments of the present application is shown.

[0059] Figure 8 The structural schematic diagram of an electrical device provided by some embodiments of the present application is shown.

[0060] In the drawings, the drawings are not necessarily drawn to actual scale.

[0061] The description of the reference numerals is as follows: 1. Battery pack; 2. Upper box body; 3. Lower box body; 4. Battery module; 5. Battery cell; 51. Shell; 52. Electrode assembly; 53. Cover plate; 101. Porous substrate; 102. First coating; 103. Second coating. Detailed implementation manners

[0062] Hereinafter, embodiments of the electrode assembly, battery cell, battery, and electrical device of the present application will be specifically disclosed in detail with reference to the accompanying drawings as appropriate. However, there may be cases where unnecessary details are omitted. For example, there are cases where details of well-known matters are omitted and repeated descriptions of actually identical structures are omitted. This is to prevent the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the accompanying drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter recited in the claims.

[0063] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a particular range. The ranges defined in this way can include the end values or not include the end values, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60 - 120 and 80 - 110 are listed for a specific parameter, ranges of 60 - 110 and 80 - 120 are also contemplated. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4, and 5 are listed, then the following ranges are all contemplated: 1 - 3, 1 - 4, 1 - 5, 2 - 3, 2 - 4, and 2 - 5. In the present application, unless otherwise specified, the numerical range "a - b" represents an abbreviated representation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0 - 5" means that all real numbers between "0 - 5" are fully listed herein, and "0 - 5" is only an abbreviated representation of these numerical combinations. Additionally, when it is stated that a certain parameter is an integer ≥2, it is equivalent to disclosing that the parameter is, for example, the integer 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0064] If there is no special instruction, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution, and such a technical solution should be considered to be included in the disclosure of the present application.

[0065] If there is no special instruction, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution, and such a technical solution should be considered to be included in the disclosure of the present application.

[0066] Unless otherwise specified, all steps of this application can be carried out sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method can include steps (a) and (b) carried out sequentially, or steps (b) and (a) carried out sequentially. For example, when it is mentioned that the method may further include step (c), it means that step (c) can be added to the method in any order. For example, the method can include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.

[0067] In this application, the terms "a plurality of" and "a variety of" mean two or more than two.

[0068] In the description of the embodiments of this application, unless otherwise specified, the first feature being "on" or "under" the second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, the first feature being "above", "over" and "on top of" the second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature has a higher horizontal height than the second feature. The first feature being "under", "beneath" and "underneath" the second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature has a lower horizontal height than the second feature.

[0069] Unless otherwise specified, the terms used in this application have the well-known meanings commonly understood by those skilled in the art.

[0070] Unless otherwise specified, the values of the various parameters mentioned in this application can be measured by various commonly used testing methods in the art. For example, they can be measured according to the testing methods given in the embodiments of this application. Unless otherwise specified, the test temperature for each parameter is 25 °C.

[0071] Unless otherwise specified, the testing instruments mentioned in this application can be operated according to the requirements of the product specification when in use.

[0072] The battery mentioned in the embodiments of this application can be a single physical module including one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in this application can include battery cells, battery modules or battery packs, etc. A battery cell is the smallest unit that makes up a battery and can independently perform the functions of charging and discharging. The battery cell can be in the shape of a cylinder, a cuboid or other shapes, and the embodiments of this application do not limit this. As Figure 1 is a battery cell 5 with a cuboid structure as an example.

[0073] When there are multiple battery cells, the multiple battery cells are connected in series, parallel or in a hybrid connection through a busbar component. In some embodiments, the battery can be a battery module; when there are multiple battery cells, the multiple battery cells are arranged and fixed to form a battery module. In some embodiments, the battery can be a battery pack, and the battery pack includes a box body and battery cells, and the battery cells or battery modules are accommodated in the box body. In some embodiments, the box body can be part of the chassis structure of a vehicle. For example, part of the box body can become at least part of the vehicle floor, or part of the box body can become at least part of the crossbeam and longitudinal beam of the vehicle.

[0074] In some embodiments, the battery can be an energy storage device. The energy storage device includes an energy storage container, an energy storage cabinet, etc.

[0075] In some embodiments, the battery cells can be assembled into a battery module, and the number of battery cells included in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module. Figure 2 is a schematic diagram of a battery module 4 as an example. As Figure 2 shown, in the battery module 4, multiple battery cells 5 can be arranged in sequence along the length direction of the battery module 4. Of course, they can also be arranged in any other way. Further, the multiple battery cells 5 can be fixed by fasteners.

[0076] Optionally, the battery module 4 can further include a housing with an accommodation space, and the multiple battery cells 5 are accommodated in the accommodation space.

[0077] In some embodiments, the above battery module can be further assembled into a battery pack, and the number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0078] Figure 3 and Figure 4 is a schematic diagram of a battery pack 1 as an example. As Figure 3 and Figure 4 shown, the battery pack 1 can include a box body and multiple battery modules 4 arranged in the box body. The box body includes an upper box body 2 and a lower box body 3. The upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery module 4. The multiple battery modules 4 can be arranged in the box body in any way.

[0079] The battery cells provided in the embodiments of the present application can be metal battery cells. For example, they can include lithium metal battery cells, lithium metal battery cells without a negative electrode, sodium metal battery cells, sodium metal battery cells without a negative electrode, etc.

[0080] An anode-free battery cell generally refers to a battery cell that is constructed without actively setting an anode active material layer on the anode side during the manufacturing process of the battery cell. For example, during the manufacturing process of the battery cell, no layer is set at the anode through processes such as coating or deposition, or the anode active material layer is formed by a carbonaceous active material layer. During the first charge, ions gain electrons on the anode side and deposit as metal on the surface of the anode current collector. During discharge, the metal can transform back into ions and return to the cathode, enabling cyclic charge and discharge. Compared with other battery cells, the anode-free battery cell can achieve a higher energy density due to the absence of an anode active material layer. In some embodiments, to improve the performance of the battery cell, some substances that can be used as anode active materials, such as carbon materials, can also be set on the anode side of the anode-free battery cell. Although these substances have a certain capacity, since their content is small and they are not used as the main anode active material in the battery cell, the battery cell thus constructed can still be regarded as an anode-free battery cell. The CB (Cell Balance) value of the anode-free battery cell is usually very small. For example, in some embodiments, the CB value of the anode-free battery cell can be less than or equal to 0.1. The CB value is the unit area capacity of the anode in the battery cell divided by the unit area capacity of the cathode. Since the anode-free battery cell does not contain or only contains a small amount of anode active material, the unit area capacity of the anode is small, and thus the CB value is very small, usually less than or equal to 0.1 for example.

[0081] The battery cell includes an electrode assembly and an electrolyte. The electrode assembly can be of a wound structure or a stacked structure, and the embodiments of the present application do not limit this.

[0082] The battery cell may further include an outer package, which can be used to encapsulate the electrode assembly and the electrolyte. The outer package can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package can also be a soft package, such as a pouch soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0083] In some embodiments, as Figure 5 shown, the outer package can include a housing 51 and a cover plate 53. The housing 51 can include a bottom plate and side plates connected to the bottom plate, and the bottom plate and the side plates enclose to form a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The electrode assembly 52 is encapsulated in the receiving cavity. The number of electrode assemblies 52 included in the battery cell 5 can be one or more, which can be adjusted according to requirements.

[0084] Embodiments of the present application provide an electrode assembly, which is used in metal batteries, such as lithium metal batteries, lithium metal batteries without a negative electrode, sodium metal batteries, sodium metal batteries without a negative electrode, etc., and can enable the battery to have high Coulomb efficiency, good cycle performance and rate performance.

[0085] The electrode assembly includes a positive electrode sheet, a negative electrode sheet and a separator. The separator includes a porous substrate and at least a first coating located on the side of the porous substrate close to the negative electrode sheet. The first coating includes a first binder, and the first binder includes one or more of poly(meth)acrylic acid, a lithiated salt of poly(meth)acrylic acid, a sodium salt of poly(meth)acrylic acid, and a modified polymer obtained by modifying the aforementioned polymer. The weight percentage content of the first binder in the first coating is greater than or equal to 40 wt%.

[0086] Poly(meth)acrylic acid refers to at least one selected from polyacrylic acid and polymethacrylic acid.

[0087] The lithiated salt of poly(meth)acrylic acid can be a partially lithiated salt or a fully lithiated salt, that is, part or all of -COOH in poly(meth)acrylic acid can be neutralized to -COOLi. Optionally, the lithiated salt of poly(meth)acrylic acid is a partially lithiated salt, that is, part of -COOH in poly(meth)acrylic acid is neutralized to -COOLi.

[0088] The sodium salt of poly(meth)acrylic acid can be a partially sodium salt or a fully sodium salt, that is, part or all of -COOH in poly(meth)acrylic acid can be neutralized to -COONa. Optionally, the sodium salt of poly(meth)acrylic acid is a partially sodium salt, that is, part of -COOH in poly(meth)acrylic acid is neutralized to -COONa.

[0089] There are usually serious dendrite problems in the negative electrode of metal batteries. The continuous growth of dendrites will shorten the life of the battery and affect the use of the battery. Especially after the battery is charged and discharged at a high rate for a long time, dendrites are more likely to grow on the negative electrode, resulting in a significant deterioration of the cycle performance and high-rate charging performance of the battery.

[0090] Starting from the structure of the separator, the present application can slow down dendrite growth and reduce the probability of dendrite formation by at least providing a first coating on the negative electrode side of the porous substrate, and thus the battery can have high reliability, high Coulomb efficiency, good cycle performance and rate performance.

[0091] The first coating includes a first binder, and the first binder includes one or more of poly(meth)acrylic acid, a lithiated salt of poly(meth)acrylic acid, a sodium salt of poly(meth)acrylic acid, and a modified polymer obtained by a modification process of the aforementioned polymer. The first binder contains polar functional groups, such as -COOH, etc., whereby the first binder can better bond the electrode sheet and the separator, and bond the porous substrate and the first coating, thus ensuring the tightness of the electrode assembly.

[0092] By disposing a first coating containing the first binder at least on the negative electrode side of the porous substrate, since the first binder contains polar functional groups such as -COOH, etc., the compatibility between the separator and the electrolyte can be improved, the wettability of the separator to the electrolyte can be enhanced, and the ionic transport impedance of the separator can be reduced.

[0093] The weight percentage content of the first binder in the first coating of the separator provided by the embodiments of the present application is greater than or equal to 40 wt%. Due to the high content of the first binder, at this time, in addition to playing a bonding role, the first binder can also react with lithium dendrites, sodium dendrites, etc. generated on the surface of the negative electrode through polar functional groups such as -COOH to play a role in eliminating dendrites; and the product after the reaction of the first binder with lithium dendrites, sodium dendrites, etc. also has good ionic conduction ability, whereby the ionic current on the surface of the negative electrode can be made uniform, the ionic concentration difference on the surface of the negative electrode can be alleviated, and thus the probability of dendrite formation can also be reduced.

[0094] The separator provided by the embodiments of the present application can play the effects of slowing down dendrite growth and reducing the probability of dendrite formation, thereby reducing the risk of internal short circuit of the battery, improving the reliability of the battery, and also improving the Coulomb efficiency and cycle capacity retention rate of the battery, and enabling the battery to perform high-rate charging. Therefore, the separator provided by the embodiments of the present application can make the metal battery have high reliability, high Coulomb efficiency, good cycle performance and rate performance.

[0095] In some embodiments, the weight percentage content of the first binder in the first coating can be 40 wt% - 60 wt%, and can be optionally 45 wt% - 55 wt%.

[0096] The content of the first binder in the first coating should not be too high. In addition to reacting with lithium dendrites, sodium dendrites, etc. generated on the surface of the negative electrode through polar functional groups such as -COOH to eliminate dendrites, the first binder may also consume some active ions. Therefore, when its content is too high, it will reduce the capacity and Coulomb efficiency of the battery to a certain extent. By adjusting the weight percentage content of the first binder in the first coating within the above range, the battery can have good rate performance while also having a high Coulomb efficiency and cycle capacity retention rate.

[0097] The first binder includes one or more of poly(meth)acrylic acid, lithiated salts of poly(meth)acrylic acid, sodium salts of poly(meth)acrylic acid, and modified polymers obtained from the foregoing polymers through a modification process. Optionally, the modification method may include one or more of block copolymerization modification, graft copolymerization modification, filling modification, and polymer melt blending modification. Graft copolymerization modification refers to grafting a polymer to introduce appropriate branches or functional side groups onto the main chain of the polymer. The grafting compound can be a monomer or a polymer. Block copolymerization modification can be regarded as a special case of graft copolymerization modification, where the grafting points are located at both ends of the polymer main chain. Filling modification refers to adding solid additives that are different from the matrix in composition and structure to the polymer matrix. Such additives are called fillers. Polymer melt blending modification refers to mixing and kneading two or more polymers to change their properties to form a new polymer with uniform performance.

[0098] In this application, when modifying a polymer body, such as poly(meth)acrylic acid, lithiated salts of poly(meth)acrylic acid, or sodium salts of poly(meth)acrylic acid, the weight of the modifier (such as a grafting compound, copolymerization compound, filler, or melt-blended polymer) needs to be less than the weight of the polymer body, and is preferably less than 50% of the weight of the polymer body.

[0099] In some embodiments, the first binder may include one or more of polyacrylic acid, polymethacrylic acid, partial lithium salts of polyacrylic acid, partial lithium salts of polymethacrylic acid, partial sodium salts of polyacrylic acid, partial sodium salts of polymethacrylic acid, polyacrylic acid-g-sodium carboxymethyl cellulose (PAA-g-CMC), partial lithium salts of polyacrylic acid-g-sodium carboxymethyl cellulose, partial sodium salts of polyacrylic acid-g-sodium carboxymethyl cellulose, poly(acrylic acid-g-polyvinylidene fluoride) (PAA-g-PVDF), poly(acrylic acid-g-polyvinyl alcohol) (PAA-g-PVA), poly(partial lithium salts of polyacrylic acid-g-polyvinylidene fluoride), poly(partial lithium salts of polyacrylic acid-g-polyvinyl alcohol), poly(partial sodium salts of polyacrylic acid-g-polyvinylidene fluoride), poly(partial sodium salts of polyacrylic acid-g-polyvinyl alcohol), polymethacrylic acid-g-sodium carboxymethyl cellulose, partial lithium salts of polymethacrylic acid-g-sodium carboxymethyl cellulose, partial sodium salts of polymethacrylic acid-g-sodium carboxymethyl cellulose, poly(methacrylic acid-g-polyvinylidene fluoride), poly(methacrylic acid-g-polyvinyl alcohol), poly(partial lithium salts of polymethacrylic acid-g-polyvinylidene fluoride), poly(partial lithium salts of polymethacrylic acid-g-polyvinyl alcohol), poly(partial sodium salts of polymethacrylic acid-g-polyvinylidene fluoride), poly(partial sodium salts of polymethacrylic acid-g-polyvinyl alcohol), amorphous calcium carbonate-polyacrylic acid hydrogel (ACC-PAA), polyacrylic acid-polyamideimide (PAA-PAI), ethylene-acrylic acid copolymer (EAA), butadiene-acrylic acid copolymer, styrene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, butadiene-methacrylic acid copolymer.

[0100] Optionally, the first binder may include one or more of polyacrylic acid, polymethacrylic acid, partial lithium salts of polyacrylic acid, partial lithium salts of polymethacrylic acid, partial sodium salts of polyacrylic acid, partial sodium salts of polymethacrylic acid, polyacrylic acid-g-sodium carboxymethyl cellulose (PAA-g-CMC), partial lithium salts of polyacrylic acid-g-sodium carboxymethyl cellulose, partial sodium salts of polyacrylic acid-g-sodium carboxymethyl cellulose, poly(acrylic acid-g-polyvinylidene fluoride) (PAA-g-PVDF), poly(acrylic acid-g-polyvinyl alcohol) (PAA-g-PVA), poly(partial lithium salts of polyacrylic acid-g-polyvinylidene fluoride), poly(partial lithium salts of polyacrylic acid-g-polyvinyl alcohol), poly(partial sodium salts of polyacrylic acid-g-polyvinylidene fluoride), poly(partial sodium salts of polyacrylic acid-g-polyvinyl alcohol), polymethacrylic acid-g-sodium carboxymethyl cellulose, partial lithium salts of polymethacrylic acid-g-sodium carboxymethyl cellulose, partial sodium salts of polymethacrylic acid-g-sodium carboxymethyl cellulose, poly(methacrylic acid-g-polyvinylidene fluoride), poly(methacrylic acid-g-polyvinyl alcohol), poly(partial lithium salts of polymethacrylic acid-g-polyvinylidene fluoride), poly(partial lithium salts of polymethacrylic acid-g-polyvinyl alcohol), poly(partial sodium salts of polymethacrylic acid-g-polyvinylidene fluoride), poly(partial sodium salts of polymethacrylic acid-g-polyvinyl alcohol).

[0101] Other types of binders, such as sodium carboxymethyl cellulose (CMC), polyvinylidene fluoride (PVDF), and polyvinyl alcohol (PVA), are grafted onto the polymer backbone of poly(meth)acrylic acid, lithium salt of poly(meth)acrylic acid, and sodium salt of poly(meth)acrylic acid, which can further improve the bonding strength of the first coating. The possible reason is that some active crosslinking sites are introduced into the network structure of the graft polymer formed after grafting, and their anchoring and bonding effects can be evenly distributed on the electrode sheet, thereby maintaining a strong mechanical bonding effect.

[0102] In some embodiments, the content of -COOH in the first binder can be greater than or equal to 0.002 mol / g.

[0103] The first binder contains -COOH, and -COOH can react with lithium dendrites, sodium dendrites, etc. generated on the surface of the negative electrode, playing a role in eliminating dendrites. Moreover, the products after the reaction of the first binder with lithium dendrites, sodium dendrites, etc. also have good ion conduction ability, thereby evenly distributing the ion flow on the surface of the negative electrode, alleviating the ion concentration difference on the surface of the negative electrode, and further reducing the probability of dendrite formation.

[0104] By adjusting the content of -COOH in the first binder within the above range, the first binder can not only better play the bonding role, bonding the electrode sheet and the separator, and bonding the porous substrate and the first coating to ensure the tightness of the electrode assembly, but also better play the effect of slowing down dendrite growth, thereby further improving the cycle performance and rate performance of the battery.

[0105] In some embodiments, the content of -COOH in the first binder can be 0.005 mol / g - 0.012 mol / g.

[0106] The content of -COOH in the first binder should not be too high. In addition to reacting with lithium dendrites, sodium dendrites, etc. generated on the surface of the negative electrode to eliminate dendrites, -COOH may also consume some active ions, thereby reducing the capacity and Coulomb efficiency of the battery to a certain extent. By adjusting the content of -COOH in the first binder within the above range, the battery can have good rate performance while also having high Coulomb efficiency and cycle capacity retention rate.

[0107] The content of -COOH in the first binder can be tested by titration.

[0108] The content of -COOH in the first binder

[0109] v is the volume of the standard solution consumed in titrating the sample, with the unit of ml; v0 is the volume of the standard solution consumed in titrating the blank, with the unit of ml; c is the concentration of the standard solution, with the unit of mol / L; m is the mass of the sample, with the unit of g.

[0110] During titration, the following steps can be carried out: Take an appropriate amount of the first binder sample and immerse it in 0.5% hydrochloric acid aqueous solution for a period of time, then wash it with deionized water until Cl - disappears. After drying the sample, store it in a desiccator; accurately weigh 1 g of the dried first binder sample, immerse it in a freshly prepared 0.1 mol / L calcium acetate solution in a 250 ml iodine flask, place it for 12 h - 17 h, shake it carefully to obtain the test solution; take 10 ml of the test solution and put it into a 250 ml conical flask, use cresol red and thymol blue as the mixed indicator, and titrate it with 0.1 mol / L NaOH standard solution until the color of the solution changes from yellow to purple rose, and record the volume of the consumed sodium hydroxide standard solution as v; at the same time, conduct a blank control test, and record the volume of the consumed sodium hydroxide standard solution as v0.

[0111] In some embodiments, the total mass percentage content of -COOLi and -COONa in the first binder can be 1% - 15%, based on the total mass of -COOH, -COOLi and -COONa being 100%. Optionally, the total mass percentage content of -COOLi and -COONa in the first binder can be 2% - 12%, 3% - 10%, 4% - 8%.

[0112] The total mass percentage content of -COOLi and -COONa in the first binder refers to the sum of the mass contents of -COOLi and -COONa in the first binder, based on the total mass of -COOH, -COOLi and -COONa in the first binder being 100%. It should be noted that this does not mean that the first binder necessarily contains these three functional groups of -COOH, -COOLi and -COONa at the same time. The first binder can also include -COOLi but not -COONa. In this case, the total mass percentage content of -COOLi and -COONa in the first binder refers to the mass content of -COOLi in the first binder, based on the total mass of -COOH and -COOLi being 100%; the first binder can also include -COONa but not -COOLi. In this case, the total mass percentage content of -COOLi and -COONa in the first binder refers to the mass content of -COONa in the first binder, based on the total mass of -COOH and -COONa being 100%.

[0113] By adjusting the total mass percentage content of -COOLi and -COONa in the first binder within the above range, the first binder can have good ionic conduction ability, thereby better homogenizing the ion flow on the negative electrode surface, alleviating the ion concentration difference on the negative electrode surface, further reducing the probability of dendrite formation, and further improving the cycle performance and rate performance of the battery.

[0114] In some embodiments, the weight-average molecular weight of the first binder can be 50,000 - 800,000, and can be optionally 150,000 - 600,000.

[0115] By adjusting the weight-average molecular weight of the first binder within the above range, the first binder can have both good adhesion performance and good solubility, and is easily and uniformly dispersed in the slurry.

[0116] In some embodiments, the first coating may further include first particulate inorganic fillers.

[0117] Considering that the improvement of the mechanical properties of the separator by only the first binder in the first coating is limited. The first particulate inorganic fillers have high mechanical strength and good heat resistance. When used in the first coating, they can resist dendrite penetration and the thermal shrinkage of the porous substrate caused by the temperature rise inside the battery. Therefore, by including the first particulate inorganic fillers in the first coating, the separator can have high mechanical strength, good puncture resistance and good heat resistance, and further reduce the risk of internal short circuit of the battery and improve the reliability of the battery.

[0118] The first particulate inorganic fillers also have good electrolyte wettability. Therefore, when the first particulate inorganic fillers are used in the first coating, the compatibility between the separator and the electrolyte can be improved, the wettability of the separator to the electrolyte can be enhanced, the ion transport impedance of the separator can be reduced, and further the cycle performance and rate performance of the battery can be improved.

[0119] In some embodiments, the first particulate inorganic fillers can react with lithium metal and / or sodium metal, and thus can also play a role in eliminating dendrites. Optionally, the first particulate inorganic fillers may include one or more of solid electrolyte materials, metal oxides, metal sulfides, metal nitrides, non-metal oxides, non-metal sulfides, non-metal nitrides, and carbon-based materials that can react with lithium metal and / or sodium metal.

[0120] Optionally, the solid electrolyte material may include lithium titanium phosphate Li x Ti y (PO4)3(0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate Li x Al y Ti z(PO4)3 (abbreviated as LATP, 0 < x < 2, 0 < y < 1, 0 < z < 3), lithium aluminum germanium phosphate Li x Al y Ge z (PO4)3 (abbreviated as LAGP, 0 < x < 2, 0 < y < 1, 0 < z < 3), lithium aluminum zirconium phosphate Li x Al y Zr z (PO4)3 (abbreviated as LAZP, 0 < x < 2, 0 < y < 1, 0 < z < 3), lithium aluminum chromium phosphate Li x Al y Cr z (PO4)3 (abbreviated as LACP, 0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y type glass (0 < x < 4, 0 < y < 13), lithium thiogermanate electrolyte Li6PS5X (X includes one or more selected from Cl, Br, I), SiS2 type glass Li x Si y S z (0 < x < 3, 0 < y < 2, 0 < z < 4), P2S5 type glass Li x P y S z (0 < x < 3, 0 < y < 3, 0 < z < 7), lithium tetrathiophosphate Li3PS4, Li7P3S 11 , lithium germanium phosphorus sulfur sulfide Li 10 GeP2S 12 , and one or more of their respective doped compounds. More optionally, the solid electrolyte material may include lithium titanium phosphate Li x Ti y (PO4)3 (0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate Li x Al y Ti z (PO4)3 (abbreviated as LATP, 0 < x < 2, 0 < y < 1, 0 < z < 3), lithium tetrathiophosphate Li3PS4, lithium germanium phosphorus sulfur sulfide Li 10 GeP2S 12 , Li6PS5Cl, Li6PS5Br, and one or more of their respective doped compounds. The doped compound is usually a product obtained by doping other elements, such as metal elements, into the compound. The type of the doped element is not particularly limited as long as it does not damage the gist of the present application.

[0121] As an example, lithium titanium phosphate Li x Ti y(PO4)3 may include LiTi2(PO4)3. As an example, lithium aluminum titanium phosphate Li x Al y Ti z (PO4)3 may include Li 1.3 Al 0.3 Ti 1.7 (PO4)3. As an example, lithium aluminum germanium phosphate may include Li 1.5 A1 0.5 Ge 1.5 (PO4)3.

[0122] The above solid electrolyte material has high mechanical strength and good heat resistance. Adding it into the first coating can improve the mechanical strength, puncture resistance and heat resistance of the separator; the above solid electrolyte material also has good ion conduction ability and electron insulation property, and also has high reactivity, so it can better eliminate dendrites, thereby further improving the reliability, Coulomb efficiency, cycle performance and rate performance of the battery.

[0123] Optionally, the metal oxide may include one or more of oxides of Fe, oxysalts of Fe, oxides of Sn, oxides of Ti, oxides of Cu, oxides of Mn, oxides of Ge, ZrO2, ZnO.

[0124] Optionally, the metal nitride may include one or more of nitrides of Fe, nitrides of Ti, nitrides of Cu, AlN.

[0125] Optionally, the non-metal oxide may include oxides of Si, SiO x (0 < x < 2).

[0126] Optionally, the non-metal nitride may include nitrides of Si.

[0127] The above materials have high mechanical strength and good heat resistance. Adding them into the first coating can improve the mechanical strength, puncture resistance and heat resistance of the separator; the above materials also have good reactivity. After contacting with lithium dendrites, sodium dendrites, etc. in the first coating, they can form monovalent metal ions such as lithium metal and sodium metal, thereby playing a role in eliminating dendrites, and further improving the reliability, Coulomb efficiency, cycle performance and rate performance of the battery.

[0128] Optionally, the carbon-based material may include one or more of graphene oxide, carbon fluoride.

[0129] The above carbon-based materials have high mechanical strength and good heat resistance. When added to the first coating, they can improve the mechanical strength, puncture resistance, and heat resistance of the separator. Graphene oxide (GO) is rich in functional groups such as hydroxyl -OH, carboxyl -COOH, and aldehyde -CHO. These functional groups can react with lithium dendrites, sodium dendrites, etc. to generate metal oxides such as lithium oxide and sodium oxide, as well as reduced graphene oxide (rGO). Therefore, using graphene oxide in the first coating can play a role in eliminating dendrites, thereby further improving the reliability, Coulomb efficiency, cycling performance, and rate performance of the battery.

[0130] In some embodiments, the weight percentage of the first particulate inorganic filler in the first coating can be 39wt% - 59wt%, and can be optionally 44wt% - 54wt%.

[0131] When the weight percentage of the first particulate inorganic filler in the first coating is within the above range, the first coating can have a good pore structure, improving the gas permeability and electrolyte wettability of the separator. It can also endow the separator with high mechanical strength, good puncture resistance, and good heat resistance, thereby enabling the battery to have high reliability, high Coulomb efficiency, good cycling performance, and rate performance.

[0132] In some embodiments, the volume distribution particle size Dv50 of the first particulate inorganic filler can be 20nm - 2000nm.

[0133] When the volume distribution particle size Dv50 of the first particulate inorganic filler is within the above range, the first coating can have a good pore structure, improving the gas permeability and electrolyte wettability of the separator. It can also make the first coating slurry have an appropriate viscosity, facilitating coating and improving the coating effect. Additionally, it can enable the first particulate inorganic filler to better adhere to the porous substrate, reducing powder dropping and pore blocking problems.

[0134] In some embodiments, the first coating may further include a first dispersant.

[0135] Optionally, the first dispersant can include one or more of hydrolyzed polymaleic anhydride, acrylic block polymer dispersants, polyester block polymer dispersants, polyethylene glycol - type polyols, polyethyleneimine, and their respective derivatives. Derivatives generally refer to products derived from the substitution of hydrogen atoms or atomic groups in polymers by other atoms or atomic groups.

[0136] Optionally, the weight - average molecular weight of the first dispersant can be less than or equal to 30,000.

[0137] Optionally, the weight percentage of the first dispersant in the first coating can be less than or equal to 2%.

[0138] A small amount of the first dispersant can make the first coating slurry more evenly dispersed, facilitating coating, and is also conducive to improving the film quality of the first coating.

[0139] In some embodiments, the thickness of the first coating can be 2 μm - 10 μm, and can be optionally 3 μm - 5 μm.

[0140] When the thickness of the first coating is within the above range, it can not only eliminate dendrites and slow down dendrite growth, but also reduce the irreversible consumption of active ions. As a result, the battery can have good rate performance while also having a high Coulomb efficiency and cycle capacity retention rate.

[0141] In some embodiments, the separator includes a porous substrate, a first coating on the side of the porous substrate close to the negative electrode sheet, and a second coating on the side of the porous substrate close to the positive electrode sheet. The second coating includes a second binder and second particulate inorganic fillers. This can better reduce the risk of internal short circuit of the battery caused by dendrite piercing through the separator and contacting the positive electrode, and further improve the reliability of the battery.

[0142] The second binder is used to bond the positive electrode sheet and the separator, and bond the porous substrate and the second coating to ensure the tightness of the electrode assembly. The second binder can adopt binder materials known in the art. In some embodiments, the second binder can include one or more of poly(meth)acrylic acid, vinylidene fluoride-based polymers, sodium carboxymethyl cellulose, styrene-butadiene rubber, and their respective derivatives. Derivatives generally refer to products derived from the substitution of hydrogen atoms or atomic groups in polymers by other atoms or atomic groups. Vinylidene fluoride-based polymers can include, but are not limited to, one or more of polyvinylidene fluoride (PVDF), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, and vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer.

[0143] In some embodiments, the second particulate inorganic fillers can include ceramics.

[0144] Optionally, the ceramics can include one or more of boehmite, Al2O3, SiO2, barium sulfate, magnesium oxide, magnesium hydroxide, calcium oxide, yttrium oxide, nickel oxide, cerium oxide, zirconium titanate, barium titanate, and magnesium fluoride.

[0145] The above-mentioned ceramics have high mechanical strength and good reducibility resistance, which can better reduce the risk of internal short circuit of the battery caused by dendrite piercing through the separator and contacting the positive electrode, and further improve the reliability of the battery.

[0146] In some embodiments, the weight percentage content of the second binder in the second coating can be 0.1 wt% - 3 wt%, and the weight percentage content of the second particulate inorganic fillers can be 97 wt% - 99.9 wt%.

[0147] In some embodiments, the volume distribution median diameter Dv50 of the second particulate inorganic filler may be 20 nm to 2000 nm.

[0148] When the volume distribution median diameter Dv50 of the second particulate inorganic filler is within the above range, the second coating can have a good pore structure, improving the gas permeability and electrolyte wettability of the separator membrane. It can also make the second coating slurry have an appropriate viscosity, facilitating coating and enhancing the coating effect. Additionally, it can enable the second particulate inorganic filler to better adhere to the porous substrate, reducing powder shedding and pore blocking problems.

[0149] In some embodiments, the thickness of the second coating can be 0.5 μm to 5 μm, and can be optionally 1 μm to 3 μm.

[0150] When the thickness of the second coating is within the above range, it can better reduce the risk of internal short circuit of the battery caused by dendrite piercing through the separator membrane and contacting the positive electrode, and further improve the reliability of the battery. It can also make the separator membrane have good gas permeability and the battery have a small impedance, thus being beneficial for the battery to have good cycle performance and rate performance.

[0151] In some embodiments, the thickness of the porous substrate can be 5 μm to 25 μm, and can be optionally 5 μm to 12 μm.

[0152] In some embodiments, the porosity of the porous substrate can be 25% to 60%, and can be optionally 30% to 50%.

[0153] When the thickness and / or porosity of the porous substrate is within the above range, the separator membrane can have good ion conduction ability and low impedance.

[0154] In some embodiments, the porous substrate may include one or more of polyolefins, polyamides, polyesters, celluloses, and their respective derivatives. Derivatives generally refer to products derived from the substitution of hydrogen atoms or atomic groups in polymers by other atoms or atomic groups.

[0155] Optionally, the polyester may include, but is not limited to, one or more of polyethylene terephthalate and polybutylene terephthalate.

[0156] Optionally, the porous substrate may include one or more of polyolefins and their derivatives. Optionally, the monomers for forming polyolefins may include, but are not limited to, one or more of ethylene, propylene, tetrafluoroethylene, vinylidene fluoride, and vinyl chloride. Optionally, the porous substrate may include polyethylene.

[0157] In some embodiments, the porous substrate can be a single-layer film structure, a multi-layer film structure, or a non-woven fabric structure.

[0158] In some embodiments, the total thickness of the separator membrane can be 7 μm - 35 μm, optionally 9 μm - 20 μm, and more optionally 10 μm - 15 μm.

[0159] In some embodiments, the porosity of the separator membrane can be 25% - 50%, optionally 30% - 45%.

[0160] When the total thickness and / or porosity of the separator membrane are within the above ranges, the separator membrane can have good ion conduction ability and low impedance.

[0161] Figure 6 The schematic structural diagram of the separator membrane provided by some embodiments of the present application is shown. Figure 7 The schematic structural diagram of the separator membrane provided by some other embodiments of the present application is shown. As Figure 6 shown, the separator membrane includes a porous substrate 101 and a first coating 102 located on one side of the porous substrate 101, and the first coating 102 is close to the negative electrode plate. As Figure 7 shown, the separator membrane includes a porous substrate 101 and a first coating 102 and a second coating 103 located on both sides of the porous substrate 101 respectively. The first coating 102 is close to the negative electrode plate, and the second coating 103 is close to the positive electrode plate.

[0162] The thicknesses of the porous substrate, the first coating, the second coating, and the separator membrane have meanings well-known in the art and can be measured by methods known in the art. For example, reference can be made to GB / T 6672 - 2001, Plastics - Films and Sheeting - Determination of Thickness by Mechanical Measurement, for measurement.

[0163] The porosity of the porous substrate and the separator membrane has a meaning well-known in the art and can be measured by methods known in the art. For example, reference can be made to GB / T 21650.2 - 2008, Determination of Pore Size Distribution and Porosity of Solid Materials by Mercury Intrusion and Gas Adsorption - Part 2: Gas Adsorption Method for Analysis of Mesopores and Macropores, for testing.

[0164] The volume - based particle size Dv50 of the material has a meaning well-known in the art and can be determined by instruments and methods known in the art. For example, reference can be made to GB / T 19077 - 2016 and conveniently determined using a laser particle size analyzer (such as Malvern Mastersizer 3000). The physical definition of Dv50 is the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%.

[0165] The weight - average molecular weight of the polymer has a meaning well-known in the art and can be determined by instruments and methods known in the art. For example, it can be determined by gel permeation chromatography.

[0166] The embodiments of the present application also provide a method for preparing a separator, which can prepare the separator provided by the embodiments of the present application.

[0167] The preparation method includes the following steps: providing a porous substrate and a first coating slurry; coating the first coating slurry at least on one side of the porous substrate close to the negative electrode sheet, and after drying, obtaining the separator.

[0168] In some embodiments, the first coating slurry includes a first binder and a first particulate inorganic filler.

[0169] Optionally, the first coating slurry may further include a first dispersant.

[0170] In some embodiments, the solvent in the first coating slurry may include, but is not limited to, one or more of deionized water, N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), N,N-dimethylacetamide (DMAC), and tetrahydrofuran (THF).

[0171] In some embodiments, the solid content of the first coating slurry may be 30%-60%, and may be optionally 35%-45%. This facilitates coating.

[0172] In some embodiments, the step of providing the first coating slurry may include the following steps: performing primary dispersion on the first binder, the first particulate inorganic filler, and the solvent to obtain a primary dispersion solution; adding a first dispersant to the obtained primary dispersion solution for secondary dispersion to obtain the first coating slurry.

[0173] Optionally, the secondary dispersion process may be ultrasonic dispersion, and stirring may be performed during the ultrasonic dispersion. Optionally, the stirring speed during the ultrasonic dispersion may be 1000 rpm - 1600 rpm, and the ultrasonic dispersion time may be 0.5 h - 3 h.

[0174] In some embodiments, the drying temperature of the first coating slurry may be 60°C - 80°C, and the drying time may be 5 h - 12 h.

[0175] In some embodiments, the coating method of the first coating slurry may include, but is not limited to, gravure offset coating, rotary spraying, dip coating, knife coating, etc.

[0176] In some embodiments, the method for preparing the separator further includes the following steps: providing a second coating slurry; coating the second coating slurry on the side of the porous substrate where the first coating is not provided (i.e., the side close to the positive electrode sheet), and after drying, obtaining the separator.

[0177] In some embodiments, the second coating slurry includes a second binder and a second particulate inorganic filler.

[0178] Optionally, the second coating slurry may further include a second dispersant.

[0179] In some embodiments, the solvent in the second coating slurry may include, but is not limited to, one or more of deionized water, N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), N,N-dimethylacetamide (DMAC), and tetrahydrofuran (THF).

[0180] In some embodiments, the solid content of the second coating slurry may be 30%-60%, optionally 35%-45%. This facilitates coating.

[0181] In some embodiments, the step of providing the second coating slurry may include the following steps: performing primary dispersion on the second binder, the second particulate inorganic filler, and the solvent to obtain a primary dispersion solution; adding a second dispersant to the obtained primary dispersion solution for secondary dispersion to obtain the second coating slurry.

[0182] Optionally, the secondary dispersion process may be ultrasonic dispersion, and stirring may be performed during the ultrasonic dispersion. Optionally, the stirring speed during the ultrasonic dispersion may be 1000 rpm - 1600 rpm, and the ultrasonic dispersion time may be 0.5 h - 3 h.

[0183] In some embodiments, the drying temperature of the second coating slurry may be 60°C - 80°C, and the drying time may be 5 h - 12 h.

[0184] In some embodiments, the coating method of the second coating slurry may include, but is not limited to, gravure offset coating, rotary spraying, dip coating, blade coating, etc.

[0185] For some raw materials used in the method for preparing the separator provided by the embodiments of the present application and parameters such as their contents, reference may be made to the separator provided by the embodiments of the present application, and details are not described herein again.

[0186] If there is no special instruction, each raw material used in the method for preparing the separator can be obtained through commercial purchase.

[0187] [Positive electrode plate]

[0188] In some embodiments, the positive electrode plate includes a positive electrode current collector and a positive electrode film layer provided on at least one surface of the positive electrode current collector and including a positive electrode active material. For example, the positive electrode current collector has two surfaces opposite to each other in its own thickness direction, and the positive electrode film layer is provided on any one or both of the two opposite surfaces of the positive electrode current collector.

[0189] In some embodiments, the positive electrode active material includes a material capable of deintercalating and intercalating lithium.

[0190] As an example, the positive electrode active material may include, but is not limited to, one or more of lithium transition metal oxides, metal chalcogenides, lithium-containing phosphates, and their respective modified compounds. Examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium titanium oxide, and their respective modified compounds. Lithium transition metal oxides may include, but are not limited to, layered structures and spinel structures. Examples of lithium-containing phosphates may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, and their respective modified compounds.

[0191] In some embodiments, in order to further improve the energy density of the battery, the positive electrode active material may include a general formula of Li a Ni b Co c M d O e D f One or more of lithium transition metal oxides and modified compounds thereof. 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M may include but is not limited to one or more of Ge, Mo, Sn, Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and D may include but is not limited to one or more of N, F, S and Cl.

[0192] In some embodiments, the positive electrode active material may include both lithium transition metal oxide and lithium-containing phosphate, thereby facilitating obtaining a battery having both large capacity and high reliability.

[0193] As an example, the positive electrode active material may include but is not limited to LiCoO2, LiNiO2, LiMnO2, LiNi 1 / 2 Mn 1 / 2O2, LiMn2O4, Li 4 / 3 Ti 5 / 3 O4、LiNi 1 / 2 Mn 1 / 2 O2、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2O2 (NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), LiNi 0.80 Co 0.15 Al 0.05 O2, LiFePO4, LiMnPO4, Li 1.13 Ti 0.57 Fe 0.3 One or more of S2.

[0194] In some embodiments, the positive electrode active material includes materials capable of deintercalating and intercalating sodium. For example, the positive electrode active material may include, but is not limited to, one or more of layered transition metal oxides (including, but not limited to, P2 type, O3 type, etc.), polyanion materials (such as phosphates, fluorophosphates, pyrophosphates, sulfates, etc.), and Prussian materials.

[0195] In some embodiments, by way of example, the positive electrode active material may include, but is not limited to, NaFeO2, NaCoO2, NaCrO2, NaMnO2, NaNiO2, Na 0.67 MO2 (M includes at least two of Fe, Co, Cr, Mn, Ni, V, Ti, Mo), NaMO2 (M includes at least two of Fe, Co, Ni, V, Ti, Mo), NaFePO4, NaMnPO4, NaCoPO4, Na4Fe3(PO4)2O7, Na3V2(PO4)2F3, Na3V2(PO4)3, Prussian blue, Prussian white, and one or more of their respective modified compounds.

[0196] The modified compounds of the above positive electrode active materials may be doping modification and / or surface coating modification of the positive electrode active materials.

[0197] In some embodiments, the positive electrode film layer may further optionally include a positive electrode conductive agent. By way of example, the positive electrode conductive agent may include, but is not limited to, one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0198] In some embodiments, the positive electrode film layer may optionally further include a positive electrode binder. As an example, the positive electrode binder may include, but is not limited to, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, polyethylene oxide, fluorinated acrylate resin, styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), carboxymethyl chitosan (CMCS), or one or more of them.

[0199] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of the metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include, but is not limited to, one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy. As an example, the polymer material base layer may include, but is not limited to, one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE).

[0200] The positive electrode film layer is usually formed by coating a positive electrode slurry on a positive electrode current collector and then drying and cold pressing. The positive electrode slurry is usually formed by dispersing a positive electrode active material, an optional positive electrode conductive agent, an optional positive electrode binder, and any other components in a solvent and stirring evenly. The solvent may be N-methylpyrrolidone (NMP), but is not limited thereto.

[0201] [Negative electrode tab]

[0202] The structure and composition of the negative electrode tab can be adjusted according to the type of battery cell.

[0203] In some embodiments, the negative electrode tab may include a negative electrode current collector and a metal layer provided on at least one surface of the negative electrode current collector. The metal material in the metal layer may include, but is not limited to, one or more of lithium metal, lithium alloy, sodium, sodium alloy.

[0204] The lithium alloy may be an alloy formed by lithium metal and other metal elements or non-metal elements. As an example, the other metal elements in the lithium alloy may include one or more elements such as tin, zinc, aluminum, magnesium, silver, gold, gallium, indium, platinum, and the non-metal elements in the lithium alloy may include one or more elements such as boron, carbon, silicon.

[0205] The sodium alloy can be an alloy formed by metallic sodium and other metallic elements or non-metallic elements. As an example, the other metallic elements in the sodium alloy can include one or more elements among tin, zinc, aluminum, magnesium, silver, gold, gallium, indium, platinum, and the non-metallic elements in the sodium alloy can include one or more elements among boron, carbon, silicon.

[0206] In some embodiments, the negative electrode tab can include a negative current collector and does not include a metal layer to assemble and form a non-negative electrode metal battery cell.

[0207] In some embodiments, in order to improve battery performance, some substances that can be used as negative electrode active materials conventionally, such as carbon materials, etc., can also be provided on the negative electrode side of the non-negative electrode metal battery cell. Although these substances have a certain capacity, since their content is small and they are not used as the main negative electrode active material in the battery cell, the battery cell thus constituted can still be regarded as a non-negative electrode metal battery cell.

[0208] In some embodiments, the negative current collector can include a metal foil, a three-dimensional porous current collector, or a composite current collector. As an example of the metal foil, copper foil, copper alloy foil, nickel foil, nickel alloy foil, aluminum foil, aluminum alloy foil can be used. As an example of the three-dimensional porous current collector, copper mesh, nickel mesh, aluminum mesh, copper foam, nickel foam, aluminum foam can be used. The composite current collector can include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material can include, but is not limited to, one or more of copper, copper alloy, aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. As an example, the polymer material base layer can include, but is not limited to, one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0209] [Electrolyte]

[0210] In some embodiments, the electrolyte uses an electrolytic solution, and the electrolytic solution includes an electrolyte salt and an organic solvent.

[0211] In some embodiments, the electrolytic solution includes anions, and the anions can include bis(fluorosulfonyl)imide anion (FSI - ), bis(trifluoromethylsulfonyl)imide anion (TFSI - ), dioxalate borate anion (BOB - ), difluorooxalate borate anion (DFOB - ), difluorodioxalate phosphate anion (DFOP - ), tetrafluorooxalate phosphate anion (TFOP - ), difluorophosphate anion (PO2F2 -) hexafluorophosphate anion (PF6 - ) tetrafluoroborate anion (BF4 - ) hexafluoroarsenate anion (AsF6 - ) trifluoromethanesulfonate anion (CF3SO3 - ) or one or more of them.

[0212] In some embodiments, the electrolyte includes cations, which may include one or more of lithium ions and sodium ions.

[0213] In some embodiments, the concentration of the electrolyte salt may be 0.3 mol / L or more, optionally 0.7 mol / L or more, and further may be 4 mol / L or less, optionally 2.5 mol / L or less, 1.7 mol / L or less. When the concentration of the electrolyte salt is within the above range, the electrolyte can have appropriate ionic conductivity.

[0214] The organic solvent may include, but is not limited to, one or more of esters, ethers, sulfones, nitriles, etc. Esters may include, but are not limited to, one or more of carbonates, phosphates, carboxylates, sulfates, sulfonates, etc. Carbonates may include cyclic carbonates and / or chain carbonates. Optionally, the carbonate may include both cyclic carbonates and chain carbonates at the same time. Chain carbonates may include low-viscosity polar chain carbonates, aliphatic branched carbonates, etc.

[0215] As an example, the organic solvent may include, but is not limited to, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS), diethyl sulfone (ESE), tetraethylene glycol dimethyl ether (TEGDME), ethylene glycol dimethyl ether (DME), 1,3-dioxolane (DOL), trimethyl phosphate, 3-methoxypropionitrile, H(CF2)2OCH3, C4F9OCH3, H(CF2)2OCH2CH3, H(CF2)2OCH2CF3, H(CF2)2CH2O(CF2)2H, CF3CHFCF2OCH3, CF3CHFCF2OCH2CH3, 2-trifluoromethylhexafluoropropyl methyl ether, 2-trifluoromethylhexafluoropropyl ethyl ether, 2-trifluoromethylhexafluoropropyl propyl ether, 3-trifluoromethyl octafluorobutyl methyl ether, 3-trifluoromethyl octafluorobutyl ethyl ether, 3-trifluoromethyl octafluorobutyl propyl ether, 4-trifluoromethyl decafluoropentyl methyl ether, 4-trifluoromethyl decafluoropentyl ethyl ether, 4-trifluoromethyl decafluoropentyl propyl ether, 5-trifluoromethyl dodecafluorohexyl methyl ether, 5-trifluoromethyl dodecafluorohexyl ethyl ether, 5-trifluoromethyl dodecafluorohexyl propyl ether, 6-trifluoromethyl tetrafluoroheptyl methyl ether, 6-trifluoromethyl tetrafluoroheptyl ethyl ether, 6-trifluoromethyl tetrafluoroheptyl propyl ether, 7-trifluoromethyl hexafluorooctyl methyl ether, 7-trifluoromethyl hexafluorooctyl ethyl ether, 7-trifluoromethyl hexafluorooctyl propyl ether, or one or more of them.

[0216] In some embodiments, the electrolyte may optionally further include additives. For example, the additives may include negative electrode film-forming additives, may also include positive electrode film-forming additives, and may further include additives that can improve certain battery performance, such as additives for improving battery overcharge performance, additives for improving battery high-temperature performance, additives for improving battery low-temperature power performance, etc.

[0217] The preparation method of battery cells is well-known. In some embodiments, a battery cell can be assembled by combining a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte. As an example, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a stacking process. The electrode assembly is placed in an outer package, dried, and then the above-mentioned electrolyte is injected. After vacuum packaging, standing, formation, and other processes, a battery cell is obtained. Multiple battery cells can further form a battery module through series connection, parallel connection, or series-parallel connection. Multiple battery modules can also form a battery pack through series connection, parallel connection, or series-parallel connection. In some embodiments, multiple battery cells can also directly form a battery pack.

[0218] An embodiment of the present application also provides an electrical device. The electrical device includes the battery provided by the embodiment of the present application. The battery can be used as the power source of the electrical device or as the energy storage unit of the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc.

[0219] The electrical device can select the type of battery according to its usage requirements, such as a battery cell, a battery module, or a battery pack.

[0220] Figure 8 It is a schematic diagram of an electrical device as an example. The electrical device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the requirements of the electrical device for high power and high energy density, a battery pack or a battery module can be used.

[0221] Another example of an electrical device can be a mobile phone, a tablet computer, a laptop computer, etc. This electrical device usually requires being thin and light, and a battery cell can be used as the power source.

[0222] Example

[0223] The following embodiments more specifically describe the content disclosed in the present application. These embodiments are only for illustrative purposes, because various modifications and changes within the scope of the content disclosed in the present application are obvious to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on weight, and all reagents used in the embodiments are commercially available or synthesized according to conventional methods and can be used directly without further treatment, and the instruments used in the embodiments are all commercially available.

[0224] Embodiment 1

[0225] Preparation of the first coating slurry

[0226] Weigh the first inorganic filler SiO powder and the first binder polyacrylic acid partial lithium salt powder proportionally, and uniformly disperse them into N-methylpyrrolidone (NMP). Then add hydrolyzed polymaleic anhydride and ultrasonically disperse it at 1100 rpm for 2 h to obtain the first coating slurry with a solid content of about 40%. The volume distribution particle size Dv50 of the SiO powder is 700 nm. The weight average molecular weight of the polyacrylic acid partial lithium salt is 200,000 - 210,000, the content of -COOH is 0.01 mol / g, and the mass percentage content of -COOLi is 5%, based on the total mass of -COOH and -COOLi being 100%. The weight ratio of the polyacrylic acid partial lithium salt, SiO, and hydrolyzed polymaleic anhydride is 49.5:49.5:1.

[0227] Preparation of the separator membrane

[0228] Coat the first coating slurry on one side of a wet PE porous substrate with a porosity of 40% and a thickness of 9 μm by gravure transfer coating, and bake it at 60°C - 65°C for about 10 h to obtain a separator membrane. The thickness of the first coating is 3 μm.

[0229] Example 2

[0230] The preparation method of the separator membrane is similar to that of Example 1, except that the weight ratio of the polyacrylic acid partial lithium salt, SiO, and hydrolyzed polymaleic anhydride in the first coating is 55:44:1.

[0231] Example 3

[0232] The preparation method of the separator membrane is similar to that of Example 1, except that the weight ratio of the polyacrylic acid partial lithium salt, SiO, and hydrolyzed polymaleic anhydride in the first coating is 60:39:1.

[0233] Example 4

[0234] The preparation method of the separator membrane is similar to that of Example 1, except that the weight ratio of the polyacrylic acid partial lithium salt, SiO, and hydrolyzed polymaleic anhydride in the first coating is 65:34:1.

[0235] Example 5

[0236] The preparation method of the separator membrane is similar to that of Example 1, except that the weight ratio of the polyacrylic acid partial lithium salt, SiO, and hydrolyzed polymaleic anhydride in the first coating is 45:54:1.

[0237] Example 6

[0238] The preparation method of the separator membrane is similar to that of Example 1, except that the weight ratio of the polyacrylic acid partial lithium salt, SiO, and hydrolyzed polymaleic anhydride in the first coating is 40:59:1.

[0239] Comparative Example 1

[0240] A wet-process PE porous membrane with a porosity of 40% and a thickness of 9 μm was used as the separator membrane.

[0241] Comparative Example 2

[0242] The preparation method of the separator membrane was similar to that of Example 1, except that the weight ratio of partial lithium salt of polyacrylic acid, SiO, and hydrolyzed polymaleic anhydride in the first coating was 30:69:1.

[0243] Comparative Example 3

[0244] The preparation method of the separator membrane was similar to that of Example 1, except that the weight ratio of partial lithium salt of polyacrylic acid, SiO, and hydrolyzed polymaleic anhydride in the first coating was 2:97:1.

[0245] Performance test of the separator membrane

[0246] (1) Puncture strength test of the separator membrane

[0247] The puncture strength of the separator membrane was tested according to GB / T36363-2018. The separator membrane was cut into samples with a width of 10 mm and a length of 150 mm, and then flattened and clamped in the fixture. A steel needle was used to perform the puncture test at a rate of 100 mm / min. After the test, the sample was taken out, and the thickness at 4 points around the needle hole was tested according to GB / T6672-2001, and the average value was taken and the puncture strength was calculated. The diameter of the steel needle was 1 mm, the radius of the spherical tip was 0.5 mm, and the surface of the steel needle was smooth, without rust, oxide layer and oil stain. During the test, the number of separator membrane samples could be more than 6, and the test results were averaged.

[0248] (2) Tensile strength test of the separator membrane

[0249] The tensile strength of the separator membrane in the transverse direction (TD) and the longitudinal direction (MD) was tested according to GB / T36363-2018. The separator membrane was cut into samples with a width of 10 mm and a length of 150 mm (the length direction was parallel to the transverse direction of the separator membrane) for testing to obtain the tensile strength of the separator membrane in the transverse direction (TD). The separator membrane was cut into samples with a width of 10 mm and a length of 150 mm (the length direction was parallel to the longitudinal direction of the separator membrane) for testing to obtain the tensile strength of the separator membrane in the longitudinal direction (MD). The test instrument could be a universal tensile machine, and the tensile rate was 50 mm / min. During the test, the number of separator membrane samples could be more than 6, and the test results were averaged.

[0250] (3) Thermal shrinkage rate test of the separator membrane

[0251] The thermal shrinkage rates in the transverse direction (TD) and longitudinal direction (MD) of the separator film were tested in accordance with GB / T36363-2018. Samples of the separator film with a width of 50 mm and a length of 100 mm were used. The temperature of the hot box was 105 °C and the heat treatment time was 1 h. After completion, the length and width of the separator film were measured, and the values were marked as a and b respectively. The thermal shrinkage rate in the longitudinal direction (MD) = [(100 - a) / 100] × 100%, and the thermal shrinkage rate in the transverse direction (TD) = [(50 - b) / 50] × 100%. When testing, the number of separator film samples can be more than 6, and the test results are averaged.

[0252] (4) Testing the air permeability value of the separator film

[0253] The air permeability value of the separator film was tested in accordance with GB / T36363-2018. The time required for 100 mL of air to pass through the separator film was used as the air permeability value of the separator film. The greater the air permeability value of the separator film, the poorer the air permeability of the separator film. When testing, the number of separator film samples can be more than 6, and the test results are averaged. The testing instrument can use the Xionggu KRK Wangyan type air permeability tester.

[0254] The test results of the separator film are shown in Table 1.

[0255] Next, after assembling the separator film into a coin cell, the charge rate performance and cycle performance were tested.

[0256] The coin cell can be prepared as follows. Lithium iron phosphate, conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) were mixed evenly in an appropriate amount of solvent N-methylpyrrolidone (NMP) according to a weight ratio of 8:1:1 to obtain the positive electrode paste; the positive electrode paste was coated on the positive electrode current collector aluminum foil and dried to obtain the positive electrode plate. In a glove box under argon protection, the positive electrode plate, separator film, and lithium sheet were assembled into a CR2430 type coin cell. The electrolyte salt of the electrolyte was LiFSI with a concentration of 1 mol / L, and the solvent of the electrolyte used ethylene glycol dimethyl ether (DME). The first coating of the separator film faced the lithium sheet.

[0257] Performance test of the button cell

[0258] At 25 °C, the coin cell was charged at a constant current of 0.1C to 3.65V, and then charged at a constant voltage of 3.65V to 0.05C; after the coin cell was left standing for 10 min, it was discharged at a constant current of 0.1C to 2.5V. After the coin cell was cycled twice according to the above method, the following performance tests were carried out.

[0259] The coin cells were charged at a constant current of 0.5C, 1C, and 2C to 3.65V respectively, and then charged at a constant voltage of 3.65V to 0.05C; after the coin cells were allowed to stand for 10 min, they were discharged at a constant current of 0.2C to 2.5V. The coin cells were cycled 100 times according to the above method to obtain the charging capacity of the 100th cycle and the discharging capacity of the 100th cycle. The Coulombic efficiency of the coin cells cycled 100 times = the discharging capacity of the 100th cycle / the charging capacity of the 100th cycle.

[0260] The coin cells were charged at a constant current of 1C to 3.65V, and then charged at a constant voltage of 3.65V to 0.05C; after the coin cells were allowed to stand for 10 min, they were discharged at a constant current of 0.2C to 2.5V to obtain the discharging capacity of the first cycle. The coin cells were cycled 100 times according to the above method to obtain the discharging capacity of the 100th cycle. The capacity retention rate of the coin cells cycled 100 times = the discharging capacity of the 100th cycle / the discharging capacity of the first cycle.

[0261] During the test, the number of coin cell samples can be more than 6, and the test results are averaged.

[0262] The test results of the coin cells are shown in Table 1.

[0263] Table 1

[0264]

[0265] From the test results in Table 1, it can be seen that by making the weight percentage of the first binder in the first coating greater than or equal to 40 wt%, the battery can have a high cycle capacity retention rate and a high Coulombic efficiency. The possible reason is that the content of the first binder is high. Thus, the first binder can not only play a binding role, bonding the negative electrode sheet and the separator, and bonding the porous substrate and the first coating to ensure the tightness of the electrode assembly, but also react with the dendrites generated on the surface of the negative electrode through polar functional groups such as -COOH to play a role in eliminating dendrites; and the product after the reaction of the first binder with the dendrites also has good ion conduction ability. Therefore, it can also evenly distribute the ion flow on the surface of the negative electrode, relieve the ion concentration difference on the surface of the negative electrode, and thus can also reduce the probability of dendrite formation. Therefore, by making the weight percentage of the first binder in the first coating greater than or equal to 40 wt%, it helps to eliminate dendrites and form a stable SEI film on the negative electrode, and further can improve the cycle capacity retention rate and Coulombic efficiency of the battery, and the improvement of the Coulombic efficiency of the battery at high rates is more obvious.

[0266] Example 7

[0267] The preparation method of the separator membrane is similar to that of Example 1, except that the weight-average molecular weight of the partial lithium salt of polyacrylic acid in the first coating is 50,000 - 60,000, the content of -COOH is 0.012 mol / g, and the mass percentage of -COOLi is 5%, based on the total mass of -COOH and -COOLi being 100%.

[0268] Example 8

[0269] The preparation method of the separator membrane is similar to that of Example 1, except that the weight-average molecular weight of the partial lithium salt of polyacrylic acid in the first coating is 790,000 - 800,000, the content of -COOH is 0.012 mol / g, and the mass percentage of -COOLi is 5%, based on the total mass of -COOH and -COOLi being 100%.

[0270] Example 9

[0271] The preparation method of the separator membrane is similar to that of Example 1, except that the weight-average molecular weight of the partial lithium salt of polyacrylic acid in the first coating is 20,000 - 30,000, the content of -COOH is 0.010 mol / g, and the mass percentage of -COOLi is 5%, based on the total mass of -COOH and -COOLi being 100%.

[0272] Table 2

[0273]

[0274] It can be seen from the test results in Table 2 that by further adjusting the weight-average molecular weight of the first binder, the performance of the battery can be further improved.

[0275] Example 10

[0276] The preparation method of the separator membrane is similar to that of Example 1, except that the first binder in the first coating is poly(acrylic acid partial lithium salt - g - sodium carboxymethyl cellulose), with a weight-average molecular weight of 260,000 - 270,000, the content of -COOH is 0.008 mol / g, and the mass percentage of -COOLi is 5%, based on the total mass of -COOH and -COOLi being 100%.

[0277] Example 11

[0278] The preparation method of the separator membrane is similar to that of Example 1, except that the first binder in the first coating is poly(acrylic acid partial lithium salt - g - vinylidene fluoride), with a weight-average molecular weight of 250,000 - 260,000, the content of -COOH is 0.006 mol / g, and the mass percentage of -COOLi is 5%, based on the total mass of -COOH and -COOLi being 100%.

[0279] Example 12

[0280] The preparation method of the separator membrane is similar to that of Example 1, except that the first binder in the first coating is poly(acrylic acid partial lithium salt-g-vinyl alcohol), with a weight average molecular weight of 340,000 - 350,000, the content of -COOH is 0.008 mol / g, and the mass percentage of -COOLi is 5%, based on the total mass of -COOH and -COOLi being 100%.

[0281] Table 3

[0282]

[0283] As can be seen from the test results in Table 3, different types of the first binders can all enable the battery to have a high cycle capacity retention rate and a high Coulomb efficiency.

[0284] Example 13

[0285] Preparation of the first coating slurry

[0286] Weigh the first inorganic filler SiO powder and the first binder polyacrylic acid partial lithium salt powder in proportion, and disperse them evenly in N-methylpyrrolidone (NMP). Then add hydrolyzed polymaleic anhydride and disperse it by ultrasonic wave at 1100 rpm for 2 h to obtain the first coating slurry with a solid content of about 40%. The volume distribution particle size Dv50 of the SiO powder is 700 nm. The weight average molecular weight of the polyacrylic acid partial lithium salt is 200,000 - 210,000, the content of -COOH is 0.01 mol / g, and the mass percentage of -COOLi is 5%, based on the total mass of -COOH and -COOLi being 100%. The weight ratio of the polyacrylic acid partial lithium salt, SiO, and hydrolyzed polymaleic anhydride is 49.5:49.5:1.

[0287] Preparation of the second coating slurry

[0288] Weigh the second inorganic filler boehmite powder and the second binder polyacrylic acid (PAA) powder in proportion, and disperse them evenly in N-methylpyrrolidone (NMP). Then add hydrolyzed polymaleic anhydride and disperse it by ultrasonic wave at 1100 rpm for 2 h to obtain the second coating slurry with a solid content of about 40%. The volume distribution particle size Dv50 of the boehmite powder is 700 nm, and the weight ratio of the boehmite, polyacrylic acid, and hydrolyzed polymaleic anhydride is 97:2:1.

[0289] Preparation of the separator membrane

[0290] The first coating slurry is coated on one side of a wet-process PE porous substrate with a porosity of 40% and a thickness of 9 μm by gravure transfer coating, and baked at 60°C - 65°C for about 10 h; then the second coating slurry is coated on the other side of the PE porous substrate in the same manner and baked at 60°C - 65°C for about 10 h to obtain a separator membrane with a three-layer structure. The thickness of the first coating is 3 μm, and the thickness of the second coating is 2 μm.

[0291] Table 4

[0292]

[0293] As can be seen from the test results in Table 4, by further providing a second coating on the positive electrode side of the porous substrate, the puncture strength, tensile strength and heat resistance of the separator membrane can be further improved, and the performance of the battery can also be further improved.

[0294] It should be noted that this application is not limited to the above embodiments. The above embodiments are only examples, and embodiments with the same structure and the same effect as the technical idea within the scope of the technical solution of this application are included in the technical scope of this application. In addition, within the scope of not departing from the gist of this application, various modifications that can be conceived by those skilled in the art to the embodiments and other ways constructed by combining some constituent elements of the embodiments are also included in the scope of this application.

Claims

1. An electrode assembly, comprising a positive electrode sheet, a negative electrode sheet, and a separator, characterized in that the separator comprises a porous substrate and at least a first coating on one side of the porous substrate close to the negative electrode sheet; the first coating comprises a first binder, and the first binder comprises one or more of poly(meth)acrylic acid, a lithiated salt of poly(meth)acrylic acid, a sodium salt of poly(meth)acrylic acid, and a modified polymer obtained by a modification process of the foregoing polymers; the weight percentage content of the first binder in the first coating is greater than or equal to 40 wt%.

2. The electrode assembly according to claim 1, characterized in that, The weight percentage content of the first binder in the first coating is 40 wt% - 60 wt%.

3. The electrode assembly according to any one of claims 1-2, characterized in that, The modification methods include one or more of block copolymerization modification, graft copolymerization modification, filling modification, and polymer melt blending modification.

4. The electrode assembly according to any one of claims 1-3, characterized in that, The first binder includes polyacrylic acid, polymethacrylic acid, partial lithium salt of polyacrylic acid, partial lithium salt of polymethacrylic acid, partial sodium salt of polyacrylic acid, partial sodium salt of polymethacrylic acid, polyacrylic acid-g-sodium carboxymethyl cellulose, partial lithium salt of polyacrylic acid-g-sodium carboxymethyl cellulose, partial sodium salt of polyacrylic acid-g-sodium carboxymethyl cellulose, poly(acrylic acid-g-vinylidene fluoride), poly(acrylic acid-g-vinyl alcohol), partial lithium salt of polyacrylic acid-g-vinylidene fluoride, partial lithium salt of polyacrylic acid-g-vinyl alcohol, partial sodium salt of polyacrylic acid-g-vinylidene fluoride, partial sodium salt of polyacrylic acid-g-vinyl alcohol, polymethacrylic acid-g-sodium carboxymethyl cellulose, partial lithium salt of polymethacrylic acid-g-sodium carboxymethyl cellulose, partial sodium salt of polymethacrylic acid-g-sodium carboxymethyl cellulose, poly(methacrylic acid-g-vinylidene fluoride), poly(methacrylic acid-g-vinyl alcohol), partial lithium salt of polymethacrylic acid-g-vinylidene fluoride, partial lithium salt of polymethacrylic acid-g-vinyl alcohol, partial sodium salt of polymethacrylic acid-g-vinylidene fluoride, partial sodium salt of polymethacrylic acid-g-vinyl alcohol, amorphous calcium carbonate-polyacrylic acid hydrogel, polyacrylic acid-polyamideimide, ethylene-acrylic acid copolymer, butadiene-acrylic acid copolymer, styrene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, butadiene-methacrylic acid copolymer, or one or more of them.

5. The electrode assembly according to any one of claims 1-4, characterized in that, The content of -COOH in the first binder is 0.005 mol / g - 0.012 mol / g.

6. The electrode assembly according to any one of claims 1-5, characterized in that, The total mass percentage content of -COOLi and -COONa in the first binder is 1% - 15%, based on the total mass of -COOH, -COOLi, and -COONa being 100%.

7. The electrode assembly according to any one of claims 1-6, characterized in that, The weight-average molecular weight of the first binder is 50,000 - 800,000.

8. The electrode assembly according to any one of claims 1-7, characterized in that, The thickness of the first coating is 2 μm - 10 μm.

9. The electrode assembly according to any one of claims 1-8, characterized in that, The first coating further comprises a first particulate inorganic filler that can react with lithium metal and / or sodium metal.

10. The electrode assembly according to claim 9, characterized in that the weight percentage content of the first particulate inorganic filler in the first coating is 39 wt% - 59 wt%; and / or, The volume distribution particle size Dv50 of the first particulate inorganic filler is 20 nm to 2000 nm; and / or, The first particulate inorganic filler includes one or more of a solid electrolyte material, a metal oxide, a metal sulfide, a metal nitride, a non-metal oxide, a non-metal sulfide, a non-metal nitride, and a carbon-based material.

11. The electrode assembly according to any one of claims 1-10, characterized in that, The separator includes a porous substrate, a first coating on a side of the porous substrate close to the negative electrode sheet, and a second coating on a side of the porous substrate close to the positive electrode sheet, and the second coating includes a second binder and a second particulate inorganic filler.

12. The electrode assembly according to claim 11, wherein The second coating satisfies at least one of the following conditions (1) to (5): (1) The weight percentage content of the second binder in the second coating is 0.1 wt% to 3 wt%, and the weight percentage content of the second particulate inorganic filler is 97 wt% to 99.9 wt%; (2) The volume distribution particle size Dv50 of the second particulate inorganic filler is 20 nm to 2000 nm; (3) The thickness of the second coating is 0.5 μm to 5 μm; (4) The second binder includes one or more of poly(meth)acrylic acid, a vinylidene fluoride polymer, sodium carboxymethyl cellulose, styrene-butadiene rubber, and their respective derivatives; (5) The second particulate inorganic filler includes ceramics.

13. The electrode assembly according to any one of claims 1-12, characterized in that, The separator satisfies at least one of the following conditions (1) to (5): (1) The total thickness of the separator is 7 μm to 35 μm; (2) The porosity of the separator is 25% to 50%; (3) The thickness of the porous substrate is 5 μm to 25 μm; (4) The porosity of the porous substrate is 25% to 60%; (5) The porous substrate includes one or more of a polyolefin, a polyamide, a polyester, a cellulose, and their respective derivatives.

14. A battery cell, characterized in that, An electrode assembly according to any one of claims 1-13.

15. The battery cell according to claim 14, wherein, The battery cell includes at least one of a lithium metal battery cell, a lithium metal battery cell without a negative electrode, a sodium metal battery cell, and a sodium metal battery cell without a negative electrode.

16. A battery, characterized in that, A battery cell according to any one of claims 14-15.

17. An electrical device, characterized in that, A battery according to claim 16, the battery being used for providing electric energy.